Falling behind: a substantive theory of care for older people with cognitive impairment in acute settings. Issue 11 (4th March 2013) - Nilsson, Anita; Rasmussen, Birgit H; Edvardsson, David
<x xml:space="preserve">Abstract</x> Aims and objectives To develop a theoretical understanding of the processes hindering person‐centred care of older people with cognitive impairment in acute care settings. Background Although person‐centred care with its holistic focus on the biopsychosocial needs of patients is commonly considered the gold standard care for older people with cognitive impairment, the extent to which care is person‐centred can increase in acute care settings generally. Design Grounded theory inspired by Strauss and Corbin. Method The study used a grounded theory approach to generate and analyse data from a Swedish sample of acute care staff, patients and family members. Results The substantive theory postulates that staff risks 'falling behind' in meeting the needs of older patients with cognitive impairment if working without consensus about the care of these patients, if the organisation is disease‐oriented and efficiency‐driven, and if the environment is busy and inflexible. This facilitated 'falling behind' in relation to meeting the multifaceted needs of older patients with cognitive impairment and contributed to patient suffering, family exclusion and staff frustration. Conclusions The theory highlights aspects of importance in the provision of person‐centred care of older people with cognitive impairment in acute settings and suggests areas to consider in the development of caring environments in which the place, pace and space can meet the needs of the older person. Relevance to clinical practice The proposed substantive theory can be used to critically examine current ward practices and routines, and the extent to which these support or inhibit high‐quality person‐centred care for older patients with known or unknown cognitive impairments.